Methyl 6-Benzyl-3-Hydroxy-3,6-Dimethyl-1,2-Dioxane-4-Carboxylate - Alexandre Benech; Omar Khoumeri; Christophe Curti; Patrice Vanelle (Molbank, 2024)
Plasmodium falciparum is a fast-evolving parasite responsible for the fatal disease malaria, making it crucial to renew our therapeutic arsenal. Modulating the artemisinin’s endoperoxide pharmacophore is a promising route to synthesizing new antimalarial derivatives. For the first step of our 20 mmol scale synthesis, catalyzed by manganese (III) acetylacetonate, we applied the conditions previously described in the literature to one of our low-yielding asymmetrically disubstituted alkenes, (2-methylallyl)benzene. Under conditions designed for alkyl derivatives, manganese (II) and (III) acetate catalyzed its peroxycyclization with methyl 3-oxobutanoate to a 1,2-dioxane ring in the presence of oxygen from air at room temperature with a 36% yield, while an oxygen atmosphere, as described in the literature, decreased the yield to 7%. Finally, under conditions designed for aryl derivatives, the yield was reduced to 30%, showing that methylallyl derivatives have an intermediate reactivity that needs further optimization to produce 1,2-dioxane ring by manganese catalyzation in good yields. This work characterizes the product obtained and discusses the most suitable reaction conditions.